Antibacterial Activity of Ethanol Extracts of N-hexane and Ethyl Acetate Fractions from Nutmeg Leaves (Myristica fragrans) on Shigella dysenteriae and Streptococcus pyogenes - Sunita, Della; Mambang, D Elysa Putri; Pulungan, Ainil Fithri; Yuniarti, Rafita (Indonesian Journal of Science and Pharmacy, 2024)
Nutmeg leaves (Myristica fragrans) have been known as a traditional medicinal plant with properties as a pain reliever, anti-inflammatory, digestive and respiratory smoothener, and antibacterial. This study aims to determine the antibacterial activity of ethanol extract, n-hexane fraction, and ethyl acetate fraction of nutmeg leaves against Shigella dysenteriae and Streptococcus pyogenes. Ethanol extract of nutmeg leaves was made by maceration method with 96% ethanol solvent and fractionated using n-hexane and ethyl acetate solvents. Antibacterial activity test against Shigella dysenteriae and Streptococcus pyogenes was carried out using the agar diffusion method. The results showed that the ethyl acetate fraction of nutmeg leaf extract produced a larger inhibition zone diameter compared to the n-hexane fraction of nutmeg leaf extract, which was 16.6 mm at a concentration of 50% for Shigella dysenteriae bacteria and 18.1 mm at a concentration of 50% for Streptococcus pyogenes bacteria, which was classified as moderate. Based on this study, the ethyl acetate fraction of nutmeg leaf extract had the best antibacterial activity against Shigella dysenteriae and Streptococcus pyogenes.